Kenneth Cragg's appreciation of the Prophethood of Muhammad (PBUH): characterizing his theological framework - Mohd. Daud, Noor Amali; Muhammad, Akilu Aliyu (2016)
Portrayal of Muhammad’s Prophethood has been a controversial theme in Muslim-Christian relations from medieval to contemporary periods. In medieval period, Prophet Muhammad (p.b.u.h) was generally portrayed negatively. However, in contemporary periods Christian attitudes towards Islam and Prophet Muhammad (p.b.u.h) started witnessing some paradigm shift. Their approaches began to shift from polemics to dialogue, from divergences to searching for commonalities and from hostilities to mutual relations. They began to delve into the biography and teachings of the Prophet (p.b.u.h) in a positive way and also appreciate his Prophethood based on their various understandings of his religious experiences. In connection to such a development, this article attempts to critically investigate and characterize the framework of Kenneth Cragg’s response to, and appreciation of Muhammad’s Prophethood. The article accentuates on his book Muhammad and the Christian: A Question of Response. This is because; this particular book varies from his earlier works and signifies a major change in his inter-religious engagement. Although his appreciation seems to be somewhat positive, there are some lapses, groundless assertions and inaccuracies which prompted the researchers to analyse and evaluate it.